Pengaruh ekspor Asia Timur terhadap pengangguran di Indonesia - Zamzami, Zamzami; Hastuti, Dwi; Sunargo, Sunargo (Jurnal Paradigma Ekonomika, 2020)
Current economic growth is seen from the ability of a country to produce goods and services that can compete with other countries. Therefore, the purpose of this study is 1) To find out developments in Asia and Indonesia in 2000-2016 and 2) To find out and analyze exports to East Asia at the unemployment rate in Indonesia. This research uses secondary data and several countries as export destinations. Indonesia such as Japan, Hong Kong, South Korea, Taiwan, China, and others. The analytical method used in this study is quantitative and quantitative descriptive. The results of this study indicate the average exports of Asian countries during the 2000-2016 period amounted to 59,328 thousand US $. In addition, the relationship between exports and unemployment has positive and negative relations. The country's export variables that have a positive and significant impact on unemployment in Indonesia are South Korea and other Asian exports. Meanwhile, exports of countries that have a negative and significant impact on unemployment are Chinese and Hong Kong exports. There are also insignificant countries that affect unemployment such as Japan despite high exports and Taiwan countries with higher export levels than Hong Kong.